Experiences and challenges with the new European Clinical Trials Regulation - Patrick-Brown, TDJH; Bourner, J; Kali, S; Trøseid, M; Yazdanpanah, Y; Olliaro, P; Olsen, IC (BioMed Central, 2024)
Background: The new European Medicines Agency (EMA) Clinical Trials Information System (CTIS), based on the Clinical Trials Regulation (CTR EU 536/2014), came into full effect on 31 January 2022 and was intended to provide an easier, more streamlined approach to the registration of clinical trials taking place in Europe. Using the experience gained on the new regulatory framework from three multi-national European clinical research studies of outbreak-prone infectious diseases, this article describes the advantages and shortcomings of the new clinical trial submission procedure.